(3HQfGeL faS MQci ddMO ef GVWQGH JTJJ GdGfJHGg h aQW GdMQcI dOi Wad GdQhVI (B= s Psychomotor program to reduce the attention deficit and hyperactivity disorder (ADHD) to kindergarten child - (3TjeGA eMeO YHOGddg eMeO lSdjeGfs; (3NGdO YHOGdQGRb GdfLGQ (B: s; (3fgi VjGA GdOjf YHOGdMejO (B: s ((3GdbGgQI (B: s (3TjeGA eMeO YHOGddg eMeO lSdjeGf (B: s, 2016)
(3HQfGeL faS MQci ddMO ef GVWQGH JTJJ GdGfJHGg h aQW GdMQcI dOi Wad GdQhVI(B. (3gOa GdOQGSI(B: (3JhXja GdCfTWI GdfaS MQcjI ai GdMO ef GVWQGH JTJJ GdGfJHGg h aQW GdMQcI ef NdGd CfTWI GdHQfGeL(B. (3ELQGAGJ GdOQGSI(B: (3Je ELQGA GdOQGSI Ydi (B(10) (3CWaGd (B(7) (3ef GdPchQ h (B(3) (3ef GdEfGK ef Phi GVWQGH JTJJ GdGfJHGg h aQW GdMQcI JQGhMJ CYeGQge ef (B(5-7) (3SfhGJ h Pdc HYO GdJCcO ef GdJTNjU GdWHi dOjge h JWHjb ebjGS fbU GVWQGH GdGfJHGg h aQW GdMQcI EYOGO (B((3cGed h HWQS(B/2010): (3h ef kKe JWHjb HQfGeL GdCfTWI GdfaS GdMQcjI Ydi YjfI GdOQGSI GdeJeKd ai (B(48) (3LdSI HhGbY (B(12) (3CSHhYG ai (B(4) (3LdSGJ CSHhYjG(B. (3fJGFL GdOQGSI(B: (3JhLO aQhb OGdI EMUGFjkG Hjf eJhSWGJ QJH OQLGJ CWaGd GdeLehYI GdJLQjHjI ai GdbjGSjf GdbHdi h GdHYOi dHQfGeL GdCfTWI GdfaS MQcjI Ydi bGFeI JTNjU GVWQGH fbU GdGfJHGg h aQW GdMQcI dWad GdQhVI dUGdM GdbjGS GdHYOi(B: (3ceG Cfg dG JhLO aQhb OGdI EMUGFjkG Hjf eJhSWGJ QJH OQLGJ CWaGd GdeLehYI GdJLQjHjI ai GdbjGSjf GdHYOi h GdJJHYi dHQfGeL GdCfTWI GdfaS MQcjI Ydi bGFeI JTNjU GVWQGH fbU GdGfJHGg h aQW GdMQcI dWad GdQhVI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdJQHjI ddWahdI GdeHcQI (B- (3bSe GdYdhe GdfaSjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GVWQGH JTJJ GdGfJHGgs; (3GVWQGH JTJJ GdGfJHGg h aQW GdMQcIs; (3GVWQGH fbU GdGfJHGgs